Infecciones vaginales y complicaciones durante el embarazo en usuarias del Centro de Salud Universitario de Motupe - Loja - González Armijos, Viviana Yomary (2021)
Vaginal infections are co-responsible for a significant percentage of maternal and perinatal morbidity due to complications such as threatened abortion, ruptured membranes, preterm delivery and pelvic inflammatory disease. This research paper resulted in the creation of clinical-epidemiological profiles, favoring medical staff and pregnant users. They contributed to the timely detection from the very first level of care, thus reducing complications and improving their quality of life. The objectives of this study were: to determine vaginal infections and complications during pregnancy; to recognize the most frequent vaginal infections; to identify complications and to establish the relationship between them. This report is a descriptive, ambispective, correlational and cross-sectional study, employing both a qualitative and quantitative approach. This was carried out at the Motupe University Health Center during the period October 2020 - March 2021. The sample consisted of 127 users and a sample of 52 pregnant women who met the inclusion criteria. Details were inputted into a data collection sheet created by the author. Results showed that Bacterial Vaginosis occurred in 15% of women between 26-30 years of age, 13% in women between 21-35 years of age, 8% in women between 36-40 years of age and 6% in women between 16-20 years of age and women aged between 31-35 years old. Tricomoniasis occurred in 6% of women aged 21-35 years of age, 2% in those aged 26-35 and Candidiasis occurred in13% of women aged 26-30 years, 9% in women aged 21-35, 8% in those aged 16-20 and 6% in those aged 31-40. With respect to complications the study showed 4% suffered from the threat of abortion and 96% did not manifest any complications as a result of these infections. From bacterial vaginosis and candidiasis infections 4.38% presented complications with respect to the threat of abortion thus demonstrating that patients with vaginal infections do not display complications in high percentages. Key Words: complications, pregnancy, vaginal infection.